Evolution of the “COVID-19” syndemia in Costa Rica as of 12/10/2021 - Mora-Alvarado, Darner A. (2022)
This study addresses the evolution of “COVID-19” in Costa Rica between 03/06/2020 and 12/10/2021, by analyzing cases and deaths associated with the coronavirus “SARS-CoV-2”, agent infectious disease of “COVID-19”. In addition, the advancement of vaccination in Costa Rica is determined, in the context of Latin America, and its impact on the number of cases, patients admitted to the Intensive Care Unit (ICU) and deaths, in the vaccination period from January 2021. On the other hand, the aspects that qualify this health crisis as a “syndemic” are identified, which is more than a pandemic due to the synergy of the infectious agent and chronic diseases or comorbidities, in the context of social inequities between the Costa Rican population. Finally, due to under-records in infections and deaths, based on estimates made by the World Health Organization (WHO), that 10% of the world’s population (780 million people) had already been infected by “SARS -CoV-2 “as of October 2020, an austere estimate of infections and deaths is made as of 12/10/2021. As a recommendation, the importance of addressing the health crisis due to “COVID-19” is indicated as a syndicate, given the effect on chronic diseases and the economic reactivation of the Costa Rican population.